Performance improvement of SISO linear control systems by hybrid state resetting and sector confinement of trajectories. (31st March 2016) - González, José Antonio; Barreiro, Antonio; Dormido, Sebastián; Falcón, Pablo
Summary: Reset control techniques have been proposed to overcome fundamental limitations of linear controllers by means of their transformation into hybrid models that combine continuous flow and discrete jump dynamics. The hybrid nature in the control loop involves some difficulties when analyzing the performance of the controller and some drawbacks on the controller design related to the stability conditions. The technique that we propose is based on sector confined target dynamics of the continuous flow mode by means of the application of the discrete reset jumps. This behavior, in the error plane ( e ( t ), ė ( t ) ), is correlated with certain preferred sectors that lead to fast and over‐damped responses. The paper studies how to design a hybrid resetting version of a linear controller that achieves the required fast and over‐damped responses to arbitrary references. Copyright © 2016 John Wiley & Sons, Ltd.